"Zdziczenie obyczajów pośmiertnych" Bolesława Leśmiana jako dramat-synteza = "The Savagery of Posthumous Mores" ["Zdziczenie obyczajów pośmiertnych"] by Bolesław Leśmian as a drama-synthesis - Wawryk, Joanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
"The Savagery of Posthumous Mores" has been present in the studies of Bolesław Leśmian's works for years, but it was not until 2014 that the first edition of the work prepared on the basis of the manuscripts was published in Dariusz Pachocki's issue. This fact prompts further attempts to analyse and interpret the work.
Keywords: Leśmian, Bolesław (1877-1937); teatr śmierci; poemat fantastyczny; poemat dramatyczny; death theatre; fantastic poem; dramatic poem